2018
DOI: 10.1029/2018jc013765
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Wind and Waves on Spreading and Mixing in the Fraser River Plume

Abstract: This study uses drifter-based observations to investigate the role of wind and waves on spreading and mixing in the Fraser River plume. Local winter wind patterns commonly result in two distinct forcing conditions, moderate winds from the southeast (SE) and strong winds from the northwest (NW). We examine how these patterns influence the spreading and mixing dynamics of the plume. Under SE winds, the plume thins, spreads, and turns to the right (north) upon exiting the river mouth. Mixing is initially intense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 64 publications
1
38
0
Order By: Relevance
“…As w eff is larger than w e , wave mixing is likely the relevant controlling process in the Quinault system. In larger systems it has been suggested that the ratio H S / h p determines the extent to which wave‐driven turbulence can affect plume mixing (Kastner et al, ). SWIFT drifters with three CT sensors that escape the surf zone measure strong stratification in the upper 1.2 m, indicating that H S / h p could be in a range where wave‐driven turbulence could affect plume mixing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As w eff is larger than w e , wave mixing is likely the relevant controlling process in the Quinault system. In larger systems it has been suggested that the ratio H S / h p determines the extent to which wave‐driven turbulence can affect plume mixing (Kastner et al, ). SWIFT drifters with three CT sensors that escape the surf zone measure strong stratification in the upper 1.2 m, indicating that H S / h p could be in a range where wave‐driven turbulence could affect plume mixing.…”
Section: Discussionmentioning
confidence: 99%
“…Stokes drift causes modest advection (hundreds of meters) of the Columbia river plume (Akan et al, ). Large plume depths relative to wave heights in the Fraser River plume shield the plume from mixing due to breaking wave‐driven turbulence (Kastner et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Deltas, estuaries and lagoons are also characterised by the presence of buoyant fluxes, sediment transport and a relatively fast morphological evolution. Many studies focused on the classification of estuarine circulation (Hansen and Rattray, 1966;Horner-Devine et al, 2015), providing tools for quantifying their main characteristics O' Donnell, 2010). The interaction between fresh and seawater leads to a number of hydrodynamic patterns, identifying water masses mechanically confined into a coherent shape close to the estuaries, with specific buoyancy, the so-called plumes.…”
mentioning
confidence: 99%
“…The interaction between fresh and seawater leads to a number of hydrodynamic patterns, identifying water masses mechanically confined into a coherent shape close to the estuaries, with specific buoyancy, the so-called plumes. Their definitions and the capability to clearly state what are their borders are still subjects of discussion O' Donnell, 2010;Falcieri et al, 2014;Horner-Devine et al, 2015 and references therein) but their interaction with coastal waters explains part of the coastal mixing processes. A certain part of river discharge is transported alongshore in downstream coastal current, while a part recirculates close to the river mouth creating an increasing area of buoyant waters, generally stabilised by tidal action (Fong and Geyer, 2002;Isobe, 2005, Chant et al, 2008.…”
mentioning
confidence: 99%
See 1 more Smart Citation